Protection To The Victims of Domestic Violence Crime (Case Study In Kudus Police) - Cipto Cipto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Family violence or who is often called it with domestic violence is a universal problem faced by a country. This research to know and analys the application of the law and protection to victims of criminal acts of domestic violence, as well as the barriers and solutions in the protection of victims of domestic violenceThis research using empirical juridical approach or commonly referred to as the Juridical Sociological. The research is specified as descriptive analytical research.The results of this study are (1) a form of protection of domestic violence victims temporary and permanent protection of the court less attention. (2) Barriers in Implementing Law Enforcement Protection of Victims of Domestic Violence, namely: a. Domestic violence is often not reported to the police, because the victims felt shame; b. If the case had no complaints are often the victim withdraws the complaint and intends to settle the case in family. The conclution in this research that the legal protection for victims of domestic violence according to Act No. 23 of 2004 on the Elimination of Violence in the household is necessary. Obstacles of domestic violence is often not reported to the police. If the case has a complaint often the victims withdraw their complaint and intend to settle cases in a family manner.Keywords: Legal Protection; Victims of Domestic Violence.